STUDY OF THE LIFE CYCLE OF THLASPI ARVENSE L. IN CENTRAL YAKUTIA - V. V. Semenova; D. N. Androsova; N. S. Danilova (Юг России: экология, развитие, 2019)
Аim. In this paper, we set out to study the life cycle of Thlaspi arvense L. in Central Yakutia.Methods. The studies were carried out in a culture at the nursery for the collection of medicinal plants of the Yakut Botanical Garden (Institute for Biological Problems of Cryolithozone SB RAS).Results. While the plant in question has a high rate of aerial part development, its underground part falls behind in terms of mass development as compared to its aerial part. The pre‐generative period lasts for 13‐17 days. Small white flowers of the plant form a corymbosepaniculate inflorescence (1.0–4.5 cm in height; 52–67 flowers per inflorescence). The plant reaches 18.0–29.0 cm in height and has 19–24 leaves. The generative state lasts for 49–55 days.Conclusions. Freshly harvested seeds of T. arvense are in non‐deep physiological dormancy; their laboratory germination rate amounted to 2%. Following 6 months of dry storage, 100% germination of seeds was noted. However, the course of germination changed dramatically becoming explosive in nature. The life cycle of T. arvense lasts for one growing season (70–76 days). Three periods and five developmental states in the ontogeny of T. arvense have been identified.